Guide to Computer Forensics and Investigations - Nelson, Bill; Phillips, Amelia; Steuart, Christopher (Cengage Learning, 2016)
Combines all-encompassing topic coverage, authoritative information from seasoned experts, powerful instructor resources, and real-world student applications - delivering the comprehensive forensics resource